5-Bromo-2-hydroxybenzaldehyde 4-ethylthiosemicarbazone - Li, Zhaoyang (International Union of Crystallography, 2013)
In the title Schiff base compound, C(10)H(12)BrN(3)OS, the C—N—N—C torsion angle is 172.07 (11)°. An intramolecular hydrogen bond exists between the hydroxy H atom and the azomethine N atom. In the crystal, pairs of hydrogen bonds involving the imino H atom and the S atom give rise to supramolecular dimers.